Wellness Tourism: Exploratory Analysis of Portuguese Consumers' Profile - Karen VILLARROEL; Alcina NUNES (Communications of International Proceedings, 2020)
Wellness tourism is a recent and fast-growing trend globally that plays a significant role in the economic development of many tourism destinations around the world. Portugal already possesses a range of wellbeing activities to offer, for instance, the thermal springs that can constitute a more authentic tourism regional/local destination. This type of tourism offer can boost regional economies, improving both tourists' and residents' quality of life. In such a context, this research work intends to understand how the Portuguese residents understand the wellness tourism activities, particularly the thermal offer and to identify a customer profile. A questionnaire was conducted, to guide businesses into the comprehension of market needs and expectations according to the customers' profile, and an exploratory statistical descriptive analysis has been applied. The results allow designing a set of strategies according to the profile defined.
Keywords: Wellness tourism; thermalism; consumer profile; Portugal.